Interlocution after liberation: Who do we interpret with and which biblical text do we read with? - West, Gerald O. (HTS teologiese studies, 2020)
This article aims to point out two seminal reflections on interlocution: Frostin’s insightful late-1980s (1988) analysis of ‘Third World’ liberation theologies and his contention that the decisive question for liberation theologies was the question of who the primary dialogue partners of liberation theology have been and should be, and Vuyani Vellem’s more recent millennial (2012) reflection on how South African Black Theology after liberation has grappled and should grapple with the notion of interlocution. My choice of these two scholars is not idiosyncratic, for Vellem uses Frostin’s work as one of his starting points. I build on this conversation, reflecting with Vellem on how we might understand the issue of interlocution within black and kindred liberation and prophetic theologies today. My particular emphasis is on biblical hermeneutics; therefore, my contribution to the conversation frames my reflections within a particular phase of Black Theology in which the Bible is most significantly problematised, what Tinyiko Maluleke refers to as the second phase of Black Theology. The conundrum Itumeleng Mosala poses for Black Theology is how the recognition of the Bible as itself – intrinsically, inherently and indelibly – ‘a site of struggle’ reconfigures interlocution. Mosala, I will argue, forces us to not only ask who we interpret with when we do Black Theology, but also ask which biblical texts we read, for not all biblical texts offer resources for liberation.Contribution: This article makes a contribution to the VukaniBantuTsohangBatho – Spirituality of Black Liberation collection in which the work of Vuyani Vellem is celebrated and critically engaged. Specifically, the article interrogates and contributes to Vuyani’s Vellem understanding of ‘locution’, and asks how this concept impacts our understanding of biblical text.